Two Polish heritage language schools in Reykjavík: What support do they get from the Icelandic and Polish governments? - Natalia Ostapiuk 2000- (2022)
With the rise of numbers of bilingual children in Iceland over the past two decades, there has been a greater need for education for children in their heritage language. Currently, the biggest migrant group in Iceland comes from Poland and with this comes a large influx of Polish children into Icelandic schools. The Polish community in Iceland wants to pass the Polish language on to the generation of children raised in Iceland, and to this purpose, a Polish language school was opened in 2008. Since then, more schools have opened, and more Icelandic compulsory schools have offered Polish lessons for their Polish students. This thesis aims to uncover how the Icelandic and Polish governments support the function and system of Polish heritage language schools in Iceland. Much of the information collected in this research was from other theses written on this topic, governmental websites, correspondence with one of the workers in the Embassy of the Republic of Poland in Iceland who works directly with the Polish schools in Iceland, and interviews with one of the founders of the Polish school in Reykjavík. The most significant results were not surprising; the Icelandic government supports the study of heritage languages but, in most cases, does not admit them to their national curriculum, recognize them in their educational system, nor support them regularly in financing. However, there is support from the Polish government, with institutions like the Centre for the Development of Polish Education Abroad (ORPEG), the Association Polish Community, and the Ministry of Education and Science of Poland.